Directive Speech Acts As A Strategy to Winning World Competition in The First M-Series Final Documentary By Team Evos Legends - Muhammad Fatahillah; Riyadi Santosa; Agus Hari Wibowo (Journal of Pragmatics Research, 2026)
The rapid evolution of competitive gaming has emphasized communication as a crucial strategy in elite tournaments. However, directive speech acts in this high-pressure environment remain largely unexplored in sociopragmatic research. This study addresses that gap by examining the sociopragmatic features of directive speech acts in professional e-sports, using the documentary EVOS Legends: Final M-Series Pertama (M1) as a case study. As findings from a single bounded case, results are specific to this context and should not be generalized to other gaming communities, e-sports titles, or media; this also means the observed patterns may be shaped by the documentary's emphasis on striking, authority-driven exchanges. Spradley's ethnographic framework, comprising domain, taxonomic, and componential analysis, was applied to organize the data and reveal relational patterns across the documentary's narrative stages. A total of 515 directive speech acts were identified and validated through an expert-led Focus Group Discussion (FGD). Taxonomic classification shows register variation shaped by situational constraints: of twenty theoretical directive types, only nine emerged, concentrated in tell (28.74%), order (21.55%), and command (17.09%). Componential mapping ties this uneven distribution to recipient design and shifting urgency within the team's temporary hierarchy; its consistency with the team's documented authority structure suggests genuine register constraints rather than mere narrative artifact. Authoritative roles use direct commands to enforce strategic plans during orientation and evaluation phases, while peers rely on implicit "tell" functions in declarative form during crisis resolution, enabled by a shared mental model (SMM) of game mechanics that lets brief utterances be read as explicit tactical moves. Rather than proposing a generalized model, this study offers a structural account of linguistic compression and cognitive alignment in one elite e-sports discourse, suggesting testable hypotheses for future research, such as whether implicit directives correlate with faster response times in peer-to-peer versus hierarchical exchanges.